The Comparison of Instant and Homemade MP-ASI to Meet Nutritional Status in Infants 6-12 Months Old at the Cio Maloleo Health Center - Yunni Kartika Kapuangan; Rifzul Maulina (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to determine the comparison of Instant and Homemade MP-ASI to meet the nutritional status of infants aged 6-12 months in the working area of Cio Maloleo Health Center. Instant MP-ASI is made based on special provisions set by the World Health Organization (WHO). The type of research used in this study is comparative research, namely comparing the mean growth value of children given Homemade MP-ASI and instant MP-ASI. The measurement scale used is a ratio scale used to determine the comparison of Instant and Homemade MP-ASI. This study uses an Independent t-test analysis. Based on the output results that have been presented, it was found that the significance value (2-tailed) is 0.348, which is greater than 0.05. Therefore, it can be concluded that there is no significant difference in the average provision of Instant and Homemade MP-ASI.